The Art of Influence: Analyzing Xi Jinping's Illocutionary Speech Acts at Bo’ao Asia Forum 2022 - Muhammad Farhan Masrur; Berliana Ulfa Faizah; Nisrina Ikananda Rahmanita; Tirza Anugerah Putri Mulia Rajagukguk; Shaoqin Xiang (Universitas Negeri Surabaya, 2023)
This research investigates the illocutionary speech acts utilized by Xi Jinping in his keynote speech at the Bo’ao Asia Forum 2022. The study aims to categorize and analyze the specific types of illocutionary speech acts used by Xi Jinping in his address titled